Optimal Adaptive Inertial Droop Control–Based Power System Frequency Regulation via Wind Farms - Chen, Yijun; Yang, Bo; Han, Yiming; He, Tingyi; He, Peng; Meng, Xian; He, Xin (Frontiers in Energy Research, 2022)
Wind farm based frequency regulation of power system has progressively attracted more attention owing to its higher power generation capacity. Among which the step start-up and adaptive inertial droop control of wind turbines with maximum power point efficiently regulates system frequency via fully utilizes the rotational kinetic energy. Besides, the coefficients of adaptive droop control and virtual inertial control will facilitate a significant influence on frequency support performance and operation status of wind turbines for the power grid. To obtain optimal control parameters, a parameter optimization framework of step start-up adaptive inertial and droop controller combined with CGO algorithm is proposed, whose effectiveness is verified by a three-area four-terminal VSC-MT-HVDCs based WFs and AC system in MATLAB/Simulink. As a result, a set of parameters with a satisfactory and comprehensive dynamic scontrol performance can be acquired by the proposed method under a 200 MW load increase compared with trial-and-error approach.